Target interception by mobile robots in a wireless sensor network - Liu, Yan. (2009)
The main objective of this project is to implement an autonomous robot namely pursuer that can collaborate with sensor network to perform pursuing. The wireless sensor network will detect the intruders, then localize intruder and pass the localization information to the pursuer robot. The pursuer will communicate with the sensor node and compute an path to intercept the intruder with obstacle avoidance capability. This project involves both the hardware and software development for the autonomous robot.